FINANCIAL PERFORMANCE OF FOREIGN BANKS IN INDIA - VINILA, T. (IJRDO - Journal of Social Science and Humanities Research, 2017)
First phase of Banking reforms, triggered by recommendations of the Narasimham Committee in 1991 and the licensing of the new private sector banks through the next two decades inaugurated an era of change. Meanwhile, the opening-up of the economy to increased participation by foreign players created greater opportunities for foreign banks to work with their multinational clients in India. In the more recent past, foreign banks have followed Indian corporate entities in their outbound expansions. The survival of the banking system in India through the financial crisis has demonstrated its strengths and most foreign banks present in India believe that India is a market with undeniable potential. However, like their predecessors, they continue to look for the best possible role they can play amidst the challenging political economy, heightened competition and changing financial services regulations. After the setting up of Foreign Banks in India, the banking sector has become competitive and customer friendly. In that, four foreign banks have set up shop in the recent past. At present, there are 43 foreign banks operating in India with a network of 334 branches. Among some circles, a doubt is sometimes expressed as to whether the regulatory environment in India is liberal in regard to the functioning of the foreign banks and whether the regulatory approach towards foreign participation in the Indian banking system is consistent with liberalized environment. Undoubtedly, the facts indicate that regulatory regime followed by the Reserve Bank in respect of foreign banks is non-discriminatory, and is, in fact, very liberal by global standards.